CONTRIBUTIONS REGARDING THE IMPROVEMENT OF PHYSICAL CONDITION ON HANDBALL PLAYERS (JUNIORS III FEMALE) - Ileana Juravle; NAWARECKI Dariusz (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
Intensive worldwide sports performance requires continuous improvement of organizational forms and methodological training of athletes at this level. The attention is focused not only on professionals improve sports training methodology at high performance but also on system of sports training improving. By modeling we understand the study phenomena with models. The model is a theoretical material that reproduce, in another scale, structure (elements and relations between them) to another system that we intend to know it.